Flavivirus infection uncouples translation suppression from cellular stress responses - Roth, Hanna; Magg, Vera; Mutz, Pascal; Klein, Philipp; Hörth, Katharina; Lohmann, Volker; Bartenschlager, Ralf; Fackler, Oliver Till; Stoecklin, Georg; Ruggieri, Alessia (mBio, 2017)
As obligate parasites, viruses strictly depend on host cell translation for the production of new progeny, yet infected cells also synthesize antiviral proteins to limit virus infection. Modulation of host cell translation therefore represents a frequent strategy by which viruses optimize their replication and spread. Here we sought to define how host cell translation is regulated during infection of human cells with dengue virus (DENV) and Zika virus (ZIKV), two positive-strand RNA flaviviruses. Polysome profiling and analysis of de novo protein synthesis revealed that flavivirus infection causes potent repression of host cell translation, while synthesis of viral proteins remains efficient. Selective repression of host cell translation was mediated by the DENV polyprotein at the level of translation initiation. In addition, DENV and ZIKV infection suppressed host cell stress responses such as the formation of stress granules and phosphorylation of the translation initiation factor eIF2α (α subunit of eukaryotic initiation factor 2). Mechanistic analyses revealed that translation repression was uncoupled from the disruption of stress granule formation and eIF2α signaling. Rather, DENV infection induced p38-Mnk1 signaling that resulted in the phosphorylation of the eukaryotic translation initiation factor eIF4E and was essential for the efficient production of virus particles. Together, these results identify the uncoupling of translation suppression from the cellular stress responses as a conserved strategy by which flaviviruses ensure efficient replication in human cells. IMPORTANCE For efficient production of new progeny, viruses need to balance their dependency on the host cell translation machinery with potentially adverse effects of antiviral proteins produced by the infected cell. To achieve this, many viruses evolved mechanisms to manipulate host cell translation. Here we find that infection of human cells with two major human pathogens, dengue virus (DENV) and Zika virus (ZIKV), leads to the potent repression of host cell translation initiation, while the synthesis of viral protein remains unaffected. Unlike other RNA viruses, these flaviviruses concomitantly suppress host cell stress responses, thereby uncoupling translation suppression from stress granule formation. We identified that the p38-Mnk1 cascade regulating phosphorylation of eIF4E is a target of DENV infection and plays an important role in virus production. Our results define several molecular interfaces by which flaviviruses hijack host cell translation and interfere with stress responses to optimize the production of new virus particles.
Gesehen am 25.04.2018